Business Strategic Realignment for a Sustainable Fashion Brand: (Study Case of House of Majik as an Upcycling Fashion Brand) - Ayularas, Bonita; Aulia Zaim , Ilma (Journal of Business and Management Review, 2024)
Research Aims: This study aims to determine and formulate business strategies for House of Majik, an upcycling fashion brand, to redefine its business model as a sustainable fashion brand. Design/methodology/approach: This study uses a conceptual framework which uses several steps and tolls, such as business environmental scanning through external analysis (PESTEL, Porter’s Five Forces, and Competitor Analysis), Internal Analysis (Value-chain Analysis), Strategy Formulation (TOWS Matrix Analysis), and Redefining Business Model through Value Proposition Canvas and Business Model Canvas approach. Research Findings: Findings suggest House of Majik to adopt focus-differentiation business strategy, as the strategy is the most appropriate to leverage the exclusivity, creativity, and uniqueness inherent in an upcycling brand. Which affirmed by the value proposition of House of Majik to offer limited editions of upcycled pieces as distinctive products with reasonable prices. Keywords: business strategy; value proposition canvas; business model canvas; sustainable fashion; upcycling fashion